CAD, CAE and CAM of solid disc brake, and the foundry process / Mohamad Izam Sahab and Jamal Nahar Musa - Sahab, Mohamad Izam; Musa, Jamal Nahar (2004)
Computer evolution today plays a major role in our technological and economical development. Rather than once only being a platform for simple word processing and spreadsheet, their evolution has made them extensively important not only to certain area or scope of work but also to technical development namely engineering. Computer use in assessing and solving engineering problem has made them is more practical rather by conventional tedious calculation method. However, for any engineering tasks or problem being solve by computer, users him or herself must possesses a strong basis; conceptually and theoretically so that computer can be effectively used. Not only during design stage (CAD), CAE and CAM enables engineering analysis and manufacturing processes to be done by numerical method. It is important thus, to be able to fully utilize these platforms as the knowledge in this area is an advantage. These theses hence will utilize CAD, CAE and CAM software for manufacturing process before proceeding to product foundry process. "CAD, CAE and CAM of Solid Disc Brake and the Foundry Process".